The Concept of Ethnography in Mafeje. Issue 1 (2nd January 2019) - Nyoka, Bongani
Abstract: In classical anthropology, the term "ethnography" refers to the scientific description of races. Yet, Archie Mafeje uses the concept of ethnography in what seems to be two ways. On the one hand, ethnography, such as he conceives of it, has socio-cultural connotations. It is his preferred substitute for the nebulous concept of "culture". On the other hand, by ethnography he seems to refer to the idea of non-disciplinarity. In other words, the concept of ethnography becomes the substitute candidate for the social sciences, as they are conventionally known. Either the concept carries both meanings or Mafeje simply equivocates. This article discusses Mafeje's concept of ethnography. First, the article contextualises the discussion by providing a broad outline of his theoretical orientation. Second, given that his use of the concept of ethnography departs from that of an anthropological research method, the concept is explained and outlined. The remainder of the article demonstrates how Mafeje sets this concept to work by discussing his study of the tributary mode of production of the pre-colonial interlacustrine kingdoms of the Great Lakes region.